Cross-resistance to UV radiation of a cisplatin-resistant human cell line: overexpression of cellular factors that recognize UV-modified DNA. - Chao, C C (1991)
A human cell line selected for cisplatin resistance (CPR) was irradiated with UV light and showed cross-resistance to UV light. Applying a modified chloramphenicol acetyltransferase assay, we observed that CPR cells acquired enhanced host cell reactivation of a transfected plasmid carrying UV damage. Gel mobility shift analysis indicated that two nuclear factors that recognize UV-modified DNA were overexpressed in CPR cells. In addition, factors that bind UV-modified DNA were independent from the factors that bind cisplatin-modified DNA. The significance of the identified binding factors, possibly DNA repair enzymes, is discussed.